Financial sector development and life insurance inclusion in India: an ARDL bounds testing approach. Issue 4 (26th January 2021) - Mathew, Biju; Sivaraman, Sunitha
Abstract : Purpose: This paper analyses the relationship between financial sector development (FSD) and life insurance inclusion in India during the period from 1971–1972 to 2016–2017. The study analyses the effect of financial deepening on life insurance inclusion in India. Design/methodology/approach: The study employs augmented Dickey–Fuller (ADF) unit roots test to check the stationarity properties of the time series data. It estimates a life insurance inclusion model using the auto-regressive distributed lag model (ARDL) bounds testing approach to cointegration. Findings: The study finds evidence of a cointegrating relationship between financial deepening and life insurance inclusion in India. A significant error correction coefficient indicates automatic adjustments to short-run disequilibrium, reinforcing the cointegrating relationship between financial sector and life insurance inclusion. Research limitations/implications: A major limitation of the study is that it excludes the first-time sum assured (FSA) contributed by the private sector life insurance companies due to lack of data availability. Practical implications: The results of the study call for faster expansion of the financial sector and provision of a low interest rate regime in the Indian economy. The study invokes the need for sufficient training to the personnel in the banking and non-banking institutions to cater to the complex needs of life insurance buyers. Originality/value: The paper estimates the link between FSD and life insurance inclusion and introduces a new measure of life insurance demand, the life insurance inclusion, measured using the FSA.